ASSOCIATIONS OF ALLOSTATIC LOAD WITH CORONARY HEART DISEASE AND DEMENTIA IN THE ENGLISH LONGITUDINAL STUDY OF AGEING. (11th November 2018) - Cadar, D; Abell, J; Hackett, R; Davies, H; Llewellyn, D; Batty, G; Steptoe, A
Abstract: We evaluated the associations between allostatic load (AL), with subsequent coronary heart disease (CHD) and dementia during 12-year follow-up in the English Longitudinal Study of Ageing. Participants (N= 4, 335) were aged ≥50 years at baseline. The AL index included five biomarker risk groups covering neuroendocrine (Insulin growth factor 1), cardiovascular (systolic and diastolic blood pressure, resting pulse rate, medication), metabolic (total cholesterol-to-HDL ratio, HbA1c, triglycerides), immune (C-reactive protein, fibrinogen) and anthropometric systems (waist-to-height ratio, obese) as measured at baseline. Except for obesity, the highest gender-specific quartile of the distribution for each biomarker was scored with 1, while the remaining groups with 0. The sum ranged from 0 to 12, with higher scores signifying higher AL, was grouped into three categories: 0 (reference group), 1–3 and 4+. CHD events were defined as myocardial infarction and angina. Dementia was determined by doctor-diagnosis combined with a positive score on the Informant Questionnaire on Cognitive Decline in the Elderly. After adjustment for a range of covariates such as age, sex, socioeconomic status and health behaviours, we found that those with a higher AL index of 4+ had a 56% increased risk of CHD (Incidence Rate Ratio (IRR) 1.56 (95% Confidence Intervals (CI) 1.08–2.24), with a significant trend p=0.01), whereas the results for dementia were inconclusive (IRR=1.16 (95% CI) 0.68–1.97)). Our results showed that a high physiological burden was related to subsequent CHD, supporting the hypothesis that a cumulative index of "biological dysregulation" could act as an early determinant of CHD.